Takayasu arteritis miss-diagnosed as thoracic outlet syndrome: A case report - Naseh Yousefi; Peyman Roomizadeh; Gholam Reza Raissi; Shahram Sadeghi; Katayoun Moradi; Shahram Rahimi-Dehgolan (Annals of Musculoskeletal Medicine - Peertechz Publications, 2020)
Takayasu Arteritis (TA) is a chronic idiopathic inflammatory vasculitis of unknown etiology that mainly involves the aorta and its major branches. In this study, we reported the case of a female patient with unilateral hand weakness that was initially misdiagnosed as TOS. However, at her most recent admission, the absence of radial pulse was noted which eventually led to the diagnosis of TA. Rarity of the disease, non-specific presentation and the absence of specific biochemical marker for TA made its early diagnosis difficult. We have tried to highlight the importance of conducting a thorough the physical examination when visiting patients with weakness, as well as the importance of considering rare differential diagnoses including TA in patients with unilateral limb paresis. TA might not manifest its typical constitutional symptoms preceding vessel involvement. Therefore a thorough clinical examination is pivotal in differentiating TA and TOS.